Advanced engineering mathematics - O'Neil, Peter V. (Cengage Learning, 2018)
ADVANCED ENGINEERING MATHEMATICS, 8E is written specifically for students like you, who are primarily interested in how to effectively apply mathematical techniques to solve advanced engineering problems. Numerous examples include illustrations of mathematical techniques as well as applications. A "Math in Context" feature clearly demonstrates how the mathematical concepts and methods you are learning relate to current engineering problems. The book is organized into seven distinctive parts to provide precise focus on the individual mathematical ideas and methods. A student solutions manual offers detailed solutions to half of the problems in the book for your use in checking your progress as well as study and review.